Who needs Access to Research? The Case of Pharmaceutical Industry - ElSabry, ElHassan; Sumikura, Koichi (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Despite what many people claim about how Open Access to scientific research will be good for society (beyond academia), the body of literature on the issue of Open Access hardly offers any evidence on that. Anecdotal evidence exists for how some practicing doctors, small companies, policymakers or patient groups can benefit from such access. Yet, there are very few formal studies to quantify or measure such benefits. This study attempts to tackle part of the issue by analyzing citations to research papers in patent documents of US pharmaceutical companies to identify variables that correlate with how much Open Access papers a company cites in its patents. The ratio of citations to OA Journals (as identified in the Directory of Open Access Journals) to all journal citations in a given patent document is treated as the dependent variable in a multiple regression analysis. The main hypothesis to be tested in this study is that the high cost of journal subscription discriminates against small companies leading them to rely more on Open Access references in researching new drugs. Several control parameters are to be included like whether the company co-owns the patent with a university or with a different company, the availability and popularity of open access journals at the year prior to patent grant and whether the patented technology is pharmaceutical or not. The main limitation to the study is that it only considers gold open access papers. While one can argue that clarifying who needs access does not matter because (if the Open Access Movement succeeds) all research will be available for anyone on the internet anyway, this study assumes that such clarification still maters. Knowing who needs access will help to determine the venues where Open Access is to be advocated, the kind of political support the Open Access Movement should get and, perhaps more importantly, who should bear the cost of making the scientific literature Open Access.